Downstream Processing of Chlamydomonas reinhardtii TN72 for Recombinant Protein Recovery - Stoffels, Laura; Finlan, Arran; Mannall, Gareth; Purton, Saul; Parker, Brenda (Frontiers in Bioengineering and Biotechnology, 2019)
The green microalga Chlamydomonas reinhardtii is under development as a production host for recombinant proteins and whole-cell therapeutics. In particular, the cell wall-reduced strain TN72 is used as a model organism for protein expression and algal synthetic biology. However, the bioprocessing characteristics of TN72 and other C. reinhardtii strains have yet to be examined. Here we use a TN72 strain expressing a protein-based antibiotic (Pal) to study the scale-up of cell harvest and product recovery. Cell harvest was examined with 100L cultures in two intermittent-discharge continuous-flow disc-stack centrifuges at flow rates of 150 – 250 L.h−1, as well as with an ultra scale-down (USD) mimic of the centrifuges. Solids recovery exceeded 99.5% and the loss of products to the supernatant was below 2 – 3%. TN72 is intact following the high shear conditions of the feed zone, however discharge from both disc-stack centrifuges resulted in full cell breakage and in the case of Pal, partial degradation in the subsequent hours. We demonstrated that shake flask cultivation and the USD centrifuge technique can be used to predict the pilot-scale clarification efficiency and product release at the centrifuge inlet for TN72, but not the cell breakage on discharge. This study outlines a number of challenges for scale-up of recombinant protein production in the microalgal host in particular for whole cell therapeutics, but also opportunities for the bioprocessing of intracellular products from TN72.